PENGARUH KEPEMIMPINAN VISIONER KEPALA SEKOLAH DAN PROFESIONALISME GURU TERHADAP KINERJA GURU - Mardawiza, Sri; Marta, Redo Andi; Rosita, Tita (STKIP Pesisir Selatan, 2025)
Visionary leadership of school principals and teacher professionalism are crucial factors in determining the success of education in schools. Teachers are responsible for the implementation of the learning process in the classroom. Therefore, continuous and sustainable improvement of teacher quality is necessary, which is inseparable from the role of the principal's leadership management This study aims to determine whether there is 1) the influence of the visionary leadership of the principal on teachers' performance; 2) the influence of teachers' professionalism on teachers' performance; and 3) the combined influence of the principal's visionary leadership and teachers' professionalism on teachers' performance. This research uses a quantitative method. The sample consists of 90 elementary school teachers from Cluster 4 in Kubung District, Solok Regency. Data was collected using a questionnaire. The data analysis techniques used were 1) descriptive quantitative analysis; and 2) multiple regression. The results of the study indicate that: 1) there is a significant influence of the principal's visionary leadership on teachers' performance; 2) there is a significant influence of teachers' professionalism on teachers' performance; and 3) there is a significant combined influence of the principal's visionary leadership and teachers' professionalism on teachers' performance.